2016
DOI: 10.1016/j.wasman.2016.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical characterisation of material fractions in residual and source-segregated household waste in Denmark

Abstract: Physico-chemical waste composition data are paramount for the assessment and planning of waste management systems. However, the applicability of data is limited by the regional, temporal and technical scope of waste characterisation studies. As Danish and European legislation aims for higher recycling rates evaluation of source-segregation and recycling chains gain importance. This paper provides a consistent up-to-date dataset for 74 physico-chemical parameters in 49 material fractions from residual and 24 ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 53 publications
2
20
0
Order By: Relevance
“…The concentrations of all metals, except for As, Fe, Cd and Ti, were within the same order of magnitude as reported in plastic waste samples by Götze et al (2016), whereas the concentrations of As, Fe, Cd and Ti were considerably lower. However, the findings in the review by Bach et al (2008) reported concentrations of Fe as low as 1.3 µg/g in PET mineral water bottles, which is within the same order of magnitude as the lowest Fe concentration measured in this study (3.40 µg/g).…”
Section: > Tablesupporting
confidence: 80%
See 4 more Smart Citations
“…The concentrations of all metals, except for As, Fe, Cd and Ti, were within the same order of magnitude as reported in plastic waste samples by Götze et al (2016), whereas the concentrations of As, Fe, Cd and Ti were considerably lower. However, the findings in the review by Bach et al (2008) reported concentrations of Fe as low as 1.3 µg/g in PET mineral water bottles, which is within the same order of magnitude as the lowest Fe concentration measured in this study (3.40 µg/g).…”
Section: > Tablesupporting
confidence: 80%
“…However, the findings in the review by Bach et al (2008) reported concentrations of Fe as low as 1.3 µg/g in PET mineral water bottles, which is within the same order of magnitude as the lowest Fe concentration measured in this study (3.40 µg/g). The highest measured Cd concentration of 167 µg/g was exceptionally high compared to several other studies (reported in Götze et al, 2016), and it also exceeded the limit value of 0.01% Cd in plastic used for electrical and electronic equipment (EU, 2011a). Nevertheless, Burnley (2007) reported Cd concentration in plastic as high as 388 µg/g; moreover, this high concentration was only measured in a single sample of reprocessed PE plastic from HHW (group 2), which is a sample that also showed remarkably high Pb and…”
Section: > Tablementioning
confidence: 50%
See 3 more Smart Citations